2018
DOI: 10.1016/j.trf.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Personality, dangerous driving, and involvement in accidents: Testing a contextual mediated model

Abstract: The present study tested the role of various personality traits in explaining dangerous driving and involvement in accidents, using a contextual mediated model (N = 311). We initially found direct effects of personality traits on dangerous driving indicators (Big-5, Dark Triad, sensation seeking, aggression, and impulsivity). Subsequently, personality variables with predictive power were tested in the mediation model. Indirect effects of anger, psychopathy and sensation seeking on the history of involvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Sensation seeking can be defined as seeking intense feelings through risk taking 56 . Sensation seeking is further associated with a range of dangerous behaviors, such as high-risk sexual behavior and aggressive driving 57,58 . Conversely, too little activation can be associated with depression 59 , which supports our finding that the optimum level of stimulation is not too high and not too low.…”
Section: Discussionmentioning
confidence: 99%
“…Sensation seeking can be defined as seeking intense feelings through risk taking 56 . Sensation seeking is further associated with a range of dangerous behaviors, such as high-risk sexual behavior and aggressive driving 57,58 . Conversely, too little activation can be associated with depression 59 , which supports our finding that the optimum level of stimulation is not too high and not too low.…”
Section: Discussionmentioning
confidence: 99%
“…We focus on aversive traits because they share common aspects, such as antagonism, callousness, and egocentrism, which leads people to care less about others ( Paulhus & Williams, 2002 ). However, it is common in the literature that the connection between traits and behaviors is mediated by ‘bridging’ variables ( Monteiro et al, 2018 ). For example, Zajenkowski et al (2020) found that perception of the COVID-19 situation was a stronger predictor of compliance with the COVID-19 regulations than traits.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that personality traits are an important factor in risky behavior among drivers. It was indicated that drivers were neurotic drivers [ 66 ] deliberately break the road traffic rules (intentional road traffic rules violation) and are involved in more accidents [ 67 , 68 , 69 ]. Neurotic and extraverted drivers are prone to aggressive behavior in road traffic [ 66 , 70 , 71 ].…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%